Model Sistem Dinamik untuk Menganalisis Rasio Biaya terhadap Pendapatan Akibat Implementasi Teknologi pada Usaha Tambak - Sefi Ayu Nirmalasari; Putri Amelia (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The fish pond farming sector plays a vital role in supporting the local economy; however, fish pond farmers’ incomes remain highly volatile due to fluctuations in production, operational costs, and water quality. This study aims to analyze the income dynamics of milkfish pond farmers and examine the impact of technology adoption on income growth. The method used is System Dynamics, involving the creation of a Causal Loop Diagram (CLD) and a Stock and Flow Diagram, simulated using STELLA software. Data were obtained through observation, interviews, and literature review. The results indicate that water quality and fish mortality rates significantly affect production and income. The application of technology helps maintain water quality, thereby stabilizing production. Additionally, the use of alternative energy sources such as solar panels can reduce operational costs. Simulation results indicate that the combination of technology and energy efficiency yields a more optimal increase in profits compared to the initial conditions. This study demonstrates that the application of technology can enhance the income of milkfish pond farmers in a more effective and sustainable manner.